1998
DOI: 10.1089/aid.1998.14.99
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HLA Alloantibody Is Found in Children But Does Not Correlate with a Lack of HIV Type 1 Transmission from Infected Mothers

Abstract: Searching for mechanisms of natural resistance to HIV infection with which to guide HIV vaccine design, we have examined antibody responses to HLA class I antigens in children of HIV-1-infected mothers. Anti-HLA antibodies are known to block HIV infectivity in vitro and can be protective against SIV challenge in macaques immunized with purified class I HLA. It was hypothesized that alloantibody to maternal HLA in children might contribute to the prevention of mother-to-child transmission of HIV-1. In fact, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…These findings confirm previous studies in Nairobi that did not find higher frequencies of class I antibodies among ESN FSWs or HIVnegative children born to seropositive mothers [13,14]. However, they are at variance with higher class I antibody levels detected among ESN drug users and in HIV-discordant couples [44,45].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings confirm previous studies in Nairobi that did not find higher frequencies of class I antibodies among ESN FSWs or HIVnegative children born to seropositive mothers [13,14]. However, they are at variance with higher class I antibody levels detected among ESN drug users and in HIV-discordant couples [44,45].…”
Section: Discussionsupporting
confidence: 90%
“…However, the alloimmune responses that are expected to result from these particular HLA polymorphisms in ESN subjects have been more difficult to detect. Anti-HLA class I alloantibodies found in FSWs and in children born to HIV-infected mothers did not correlate with HIV protection [13,14]. To date, cellular alloimmune responses and their role in protection against HIV have not been studied in ESN subjects.…”
Section: Introductionmentioning
confidence: 96%
“…Consequently, it may contain HLA antibodies because several allo-HLA antibodies are known to occur naturally in the sera of both men (nonalloimmunized) and women. [9][10][11][12][13] MoralesBuenrostro et al 11 demonstrated the specificities and incidence of these allo-HLA-I Abs in nonalloimmunized males. Neither the origin nor cause of anti-HLA Abs occurring in healthy individuals has been established.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, however, no protective role of anti-HLA antibodies against HIV-1 was observed. Anti-HLA alloantibodies found in children did not correlate with a lack of HIV-1 transmission from the infected mother (16). Similarly, the presence of anti-HLA antibodies did not correlate with resistance to HIV-1 infection by female commercial sex workers in the Nairobi cohort (17).…”
mentioning
confidence: 77%